Pro Puppet - Krum, Spencer. (Apress : Imprint: Apress, 2013)
Pro Puppet, Second Edition, now updated for Puppet 3, is an in-depth guide to installing, using, and developing the popular configuration management tool Puppet. Puppet provides a way to automate everything from user management to server configuration. You'll learn how Puppet has changed in the latest version, how to use it on a variety of platforms, including Windows, how to work with Puppet modules, and how to use Hiera. Puppet is a must-have tool for system administrators, and Pro Puppet will teach you how to maximize its capabilities and customize it for your environment. Install and configure Puppet to immediately start automating tasks and create reporting solutions Learn insider tricks and techniques to better manage your infrastructure Become a Puppet expert!